2022
DOI: 10.1002/ehf2.13840
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic significance of serum chloride level in heart failure patients with preserved ejection fraction

Abstract: AimsThe prognostic value of serum chloride level has been reported primarily in patients with heart failure with reduced ejection fraction, and hence, there is limited evidence in patients of heart failure with preserved ejection fraction (HFpEF). This study was conducted to clarify the relationship between serum chloride level and clinical outcomes in patients with HFpEF with acute decompensated heart failure (ADHF). Methods and resultsPatient data were extracted from The Prospective mUlticenteR obServational… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
17
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 27 publications
(29 reference statements)
1
17
0
1
Order By: Relevance
“…The hypochloraemia that we observed in our patients can be explained both using diuretics and by the activation of the RAAS and vasopressin. We attribute less importance to other drugs given that only 50% of the patients were taking angiotensin‐converting enzyme inhibitor (ACE‐I)/angiotensin receptor blocker (ARB) and 15% mineralocorticoid receptor antagonist (MRA) and none tolvaptan, unlike other studies where this percentage was higher 14 …”
Section: Discussionmentioning
confidence: 94%
See 3 more Smart Citations
“…The hypochloraemia that we observed in our patients can be explained both using diuretics and by the activation of the RAAS and vasopressin. We attribute less importance to other drugs given that only 50% of the patients were taking angiotensin‐converting enzyme inhibitor (ACE‐I)/angiotensin receptor blocker (ARB) and 15% mineralocorticoid receptor antagonist (MRA) and none tolvaptan, unlike other studies where this percentage was higher 14 …”
Section: Discussionmentioning
confidence: 94%
“…The pathophysiology of chloride in HF is not fully understood. It is known that chloride plays a key role in the alterations of the RAAS, in the maintenance of the acid–base balance, and in the renal transporters on which diuretics act 14,18 . There are two main mechanisms that reduce chloride levels in HF: the use of diuretics and the activation of RAAS and/or vasopressin 9 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…7,8 After the publication of these two studies, several other groups confirmed these initial findings and also found that they extend to other HF phenotypes, such as patients with preserved ejection fraction. 18,19 Interestingly, despite the strong association of serum chloride with HF outcomes, the addition of chloride on top of prognostic models is either associated with little improvement in the predictive ability of the models or is not associated with an improvement at all. 9,20 This latter finding suggests that the incremental usefulness of chloride over existing models might only be valid for some subgroups, and indeed Ferreira et al have found that the usefulness of hypochloremia as a risk marker is limited to those with low sodium at baseline.…”
Section: Discussionmentioning
confidence: 99%